A special youth sanction - Vestergaard, Jørn (Journal of Scandinavian studies in criminology and crime prevention, 2004)
Under the label 'youth sanction' (ungdomssanktion) a new type of sentence for juvenile offenders has been enacted by a 2001 amendment to the Danish Penal Code. The study reported here is an analysis of the 55 sentences imposed over the first year. Widespread disparity and disproportionality in sentencing was found. Statutory requirements regarding the seriousness of the individual case have not in all instances been satisfactorily established. The emergence of the new sanction implies a considerable increase in the intensity of intervention. Being based on a revitalized treatment ideology, the new criminal sanction legitimizes a vast widening of the control measures directed against troubled youth, in particular such offenders who has another ethnic background than Danish. No comprehensive programme or coherent vision regarding treatment methods has been stipulated, and professionals are bewildered and in disagreement regarding such issues. Nothing indicates that the costly efforts will prove to be adequate as rehabilitative and crime preventive tools. The introduction of the youth sanction is part of a contemporary criminal policy agenda dominated by a broad political coalition with an urge to demonstrate ability and readiness to cope with juvenile street crime by employing more 'consequent' measures, involving tougher and swifter punishment combined with coerced rehabilitation